Enhancing Consumer Satisfaction: E-Service Quality, E-Trust, E-Wom, and Linkaja Sharia Services - Oktafeza, Arinda; Akmal, Huriyatul; Adilla Arsyi, Wushi (Al Urwah : Sharia Economics Journal, 2024)
This study investigates what influences consumer satisfaction with LinkAja Sharia Services, focusing on how user decisions play a role. It looks at factors like E-service quality, E-trust, and E-wom (electronic word-of-mouth) and how they affect user decisions and satisfaction. Utilizing Probability Sampling with a sample size of 165 respondents using the Simple Random Sampling method, the findings show that while E-service quality and E-trust have minor effects on user decisions, E-wom has a significant positive influence. E-service quality and E-trust positively impact consumer satisfaction, but E-wom has a negative effect. Interestingly, user decisions play a big part in consumer satisfaction, but they do not mediate the impact of E-service quality and E-trust on satisfaction. However, E-wom does mediate this impact significantly. Overall, this study sheds light on various factors affecting consumer satisfaction with LinkAja Sharia Services, offering insights for service providers to improve user experience and satisfaction.